2007
DOI: 10.1007/s10545-007-0616-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of the respiratory involvement in Anderson–Fabry disease

Abstract: We have demonstrated a clinically relevant age- and sex-dependent progressive pulmonary involvement in AFD patients. The effects of enzyme replacement therapy on pulmonary involvement remain to be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 19 publications
0
49
1
4
Order By: Relevance
“…In men, a significant decrease in all spirometric variables, including a reduced diffusion capacity, has been observed compared with unaffected controls (Magage et al 2007), while women have decreased percent fixed vital capacity. The primary mechanism is likely to be Gb3 accumulation within the endothelial and bronchial smooth muscle cells resulting in hyperplasia of the pulmonary small airways combined with impaired smooth muscle relaxation (Magage et al 2007;Raiman and Clarke 2010;Franzen et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…In men, a significant decrease in all spirometric variables, including a reduced diffusion capacity, has been observed compared with unaffected controls (Magage et al 2007), while women have decreased percent fixed vital capacity. The primary mechanism is likely to be Gb3 accumulation within the endothelial and bronchial smooth muscle cells resulting in hyperplasia of the pulmonary small airways combined with impaired smooth muscle relaxation (Magage et al 2007;Raiman and Clarke 2010;Franzen et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…Hence, in patients with FD, mainly small and medium sized bronchi, and potentially other pulmonary structures may become involved with ongoing disease process [20]. Additionally, the typical radiological feature of small airway disease have been shown in the case report by Kim et al demonstrating bilaterally severe mosaic attenuation pattern, which is due to a combination of ground-glass opacities and air trapping [13].…”
Section: Pulmonary Involvement In Fabry Disease -A Matter Of Bronchiomentioning
confidence: 95%
“…Of these, nine (36%; including five smokers) were found to have significant airway obstruction on spirometry, which was considered to be the result from fixed narrowing of the airway by accumulated glycosphingolipids [15]. Later studies confirmed the evidence of pulmonary involvement in terms of obstructive lung disease in patients with FD [16][17][18][19][20].…”
Section: Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations